Emotional Intelligence and Stress Coping Strategies of Medical Residents - Gintarė Montvilaitė; Dalia Antinienė (Lithuanian Sports University, 2020)
Background. Everyday medical residents experience stress related to academic, professional, and personal factors (Alosaimi, Alghamdi, Aladwani, Kazim, & Almufleh, 2016; Dave, Parikh, Vankar, & Valipay, 2018), therefore it is important to take care of their psychosocial well-being. Traits of medical residents that are important for well-being are related to control of emotional information, and abilities that provide for effective handling of stressful situations are important as well. The objective of the present study was to assess correlations between emotional intelligence and stress coping strategies of medical residents.    Methods. The study sample consisted of medical residents (n = 108). The following questionnaires were used: TEIQue-SF and Coping Styles Questionnaire. Questionnaires were sent to personal electronic addresses and target groups of social networks. Paper-based questionnaires were presented in the work and gathering places of subjects. Results. Emotional intelligence was higher than average, and the most expressed trait was the overall sense of well-being (in relation to emotionality, self-control and sociability). Sociability and self-control were more expressed in men than in women. Rational coping with stress was the most characteristic for medical residents (in relation to emotional coping, detached and avoidance coping). Women were more than men inclined to use emotional coping while men were more inclined than women to use detached coping. Conclusions. Statistically significant correlation existed between emotional intelligence and stress coping strategies of medical residents. Positive correlation was determined between emotional intelligence and adaptive stress coping strategies, while negative correlation was observed between emotional intelligence and maladaptive stress coping strategies.  Keywords: resident doctors, stress, emotional intelligence as a trait, coping with stress.